Using citizen science gamification in agriculture collaborative knowledge production - Martin, Jonathan
ANONYMOUS PROJECT is an international project run by 16 research institutions. The project’s main goal is empowering agriculture production systems through innovative knowledge-based ICT solutions to deal with high risk and uncertain conditions. In this context, a Semantic Mediawiki is desired to support the various stakeholders in the agriculture value chain in the task of capturing and sharing agricultural best practices. Applying gamification to Wikis is one strategy to encourage the community to participate, and It could be achieved by attaching Metagame, a gamification layer system. However, It could be risky because the tunning of a gamification system in the production face of the wiki could be perceived by the users as a bug in the system. To avoid this situation, a simulation based on the real historical data of the Agriculture community in Wikipedia from 2001 to 2018 was performed. The simulation revealed that is not obvious to generate a system of awards on the type of actions carried out by the Wikipedia editors. The construction of knowledge is done in very small portions, and some of them can be confused with improvements or corrections instead of contributions. Indeed, It shows the importance of tuning the reward parameters, because that allows advancing in the Metagame rank evolution.